Un-Roman sex gender, sexuality, and lovemaking in the Roman provinces and frontiers - Ivleva, Tatiana 1982-; Collins, Rob 1977- (Routledge monographs in classical studies, 2022)
Un-Roman Sex explores how gender and sex were perceived and represented outside the Mediterranean core of the Roman Empire. The volume critically explores the gender constructs and sexual behaviours in the provinces and frontiers in light of recent studies of Roman erotic experience and flux gender identities. At its core, it challenges the unproblematised extension of the traditional Romano-Hellenistic model to the provinces and frontiers. Did sexual relations and gender identities undergo processes of "provincialisation" or "barbarisation" similar to other well-known aspects of cultural negotiation and syncretism in provincial and border regions, for example in art and religion? The 11 chapters that make up the volume explore these issues from a variety of angles, providing a balanced and rounded view through use of literary, epigraphic, and archaeological evidence. Accordingly, the contributions represent new and emerging ideas on the subject of sex, gender, and sexuality in the Roman provinces.As such, Un-Roman Sex will be of interest to higher-level undergraduates and graduates/academics studying the Roman empire, gender, and sexuality in the ancient world and at the Roman frontiers